2017
DOI: 10.1016/j.neubiorev.2016.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Understanding epigenetic architecture of suicide neurobiology: A critical perspective

Abstract: Current understanding of environmental cross-talk with genetic makeup is found to be mediated through an epigenetic interface which is associated with prominent reversible and heritable changes at gene expression level. Recent emergence of epigenetic modulation in shaping the genetic information has become a key regulatory factor in answering the underlying complexities associated with several mental disorders. A comprehensive understanding of the pertinent changes in the epigenetic makeup of suicide phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 249 publications
0
18
0
2
Order By: Relevance
“…Likewise, repressive hypermethylation of the BDNF gene was detected in the blood of depressed patients compared to controls, the levels of changes being further associated with previous history of suicidal attempts, ideation, and poor response to antidepressant treatment . Finally, numerous studies have identified DNA methylation differences in the epigenetic status of the BDNF or its cognate receptor TRKB genes in peripheral blood of patients from other psychiatric disorders with depressive features and in post‐mortem brains from suicide‐completers, including those with MDD, BD, SCZ, and BPD . Likewise, the gene encoding the serotonin transporter, defined by different names, such as 5‐HTT , SLC6A4 and SERT , has been shown to display epigenetic changes in relation to several environmental stressors occurring throughout life, neuroimaging variables (volume and network of limbic tissues), as well as psychopathological disorders, such as MDD, BD, PTSD, SCZ, attention deficit hyperactivity disorder (ADHD), and addiction (reviewed in detail by Palma‐Gudiel and Fañanás ).…”
Section: Potential Use Of Epigenetics For Mechanistic Insight and Novmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, repressive hypermethylation of the BDNF gene was detected in the blood of depressed patients compared to controls, the levels of changes being further associated with previous history of suicidal attempts, ideation, and poor response to antidepressant treatment . Finally, numerous studies have identified DNA methylation differences in the epigenetic status of the BDNF or its cognate receptor TRKB genes in peripheral blood of patients from other psychiatric disorders with depressive features and in post‐mortem brains from suicide‐completers, including those with MDD, BD, SCZ, and BPD . Likewise, the gene encoding the serotonin transporter, defined by different names, such as 5‐HTT , SLC6A4 and SERT , has been shown to display epigenetic changes in relation to several environmental stressors occurring throughout life, neuroimaging variables (volume and network of limbic tissues), as well as psychopathological disorders, such as MDD, BD, PTSD, SCZ, attention deficit hyperactivity disorder (ADHD), and addiction (reviewed in detail by Palma‐Gudiel and Fañanás ).…”
Section: Potential Use Of Epigenetics For Mechanistic Insight and Novmentioning
confidence: 99%
“…The recent advancement in epigenome‐wide analyses has advanced the field beyond a gene‐candidate approach towards a more comprehensive mapping of the neuroepigenome. In this regard, life exposure‐ and phenotype‐specific epigenome signatures are constantly being generated, as in the case of childhood maltreatment, MDD, BD, SCZ, autism spectrum disorder, eating disorders and shared features, such as suicidality or psychosis . These epigenomic studies have uncovered dysregulation of multiple biological pathways, including the previously identified HPA, monoaminergic, and neurotrophin systems.…”
Section: Potential Use Of Epigenetics For Mechanistic Insight and Novmentioning
confidence: 99%
See 1 more Smart Citation
“…Among epigenetic mechanisms, DNA methylation is the most widely studied, and has been so far associated to different psychiatric disorders such as major depressive disorder (Brown et al 2019), schizophrenia (Pries et al 2017), and suicide (Roy & Dwivedi 2017). In the process of DNA methylation, one methyl group is added on the 5C position of a cytosine.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Furthermore, certain psychiatric drug treatments for BD and suicidal behavior have been shown to alter the epigenetic landscape of patients (Houtepen, van Bergen, Vinkers, & Boks, ). Looking at genes previously associated with these phenotypes, numerous candidate gene studies have sought to identify differential methylation patterns in the postmortem brains of individuals with BD and/or suicide (reviewed in Ludwig & Dwivedi, ; Roy & Dwivedi, ; Turecki, ). Correspondingly, using a hypothesis‐free approach, several studies have sought to identify DNA methylation differences throughout the genome in brain tissue samples of BD subjects with notable results providing evidence for genes such as Catenin Alpha 2 ( CTNNA2 ) (Abdolmaleky et al, ; Chen et al, ; Dempster et al, ; Mill et al, ; Ruzicka, Subburaju, & Benes, ; Xiao et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%